Top-Down Cognitive and Linguistic Influences on the Suppression of Spontaneous Otoacoustic Emissions - Marian, Viorica; Lam, Tuan Q.; Hayakawa, Sayuri; Dhar, Sumitrajit (Frontiers in Neuroscience, 2018)
Auditory sensation is often thought of as a bottom-up process, yet the brain exerts top-down control to affect how and what we hear. We report the discovery that the magnitude of top-down influence varies across individuals as a result of differences in linguistic background and executive function. Participants were 32 normal-hearing individuals (23 female) varying in language background (11 English monolinguals, 10 Korean-English late bilinguals, and 11 Korean-English early bilinguals), as well as cognitive abilities (working memory, cognitive control). To assess efferent control over inner ear function, participants were presented with speech-sounds (e.g., /ba/, /pa/) in one ear while spontaneous otoacoustic emissions (SOAEs) were measured in the contralateral ear. SOAEs are associated with the amplification of sound in the cochlea, and can be used as an index of top-down efferent activity. Individuals with bilingual experience and those with better cognitive control experienced larger reductions in the amplitude of SOAEs in response to speech stimuli, likely as a result of greater efferent suppression of amplification in the cochlea. This suppression may aid in the critical task of speech perception by minimizing the disruptive effects of noise. In contrast, individuals with better working memory exert less control over the cochlea, possibly due to a greater capacity to process complex stimuli at later stages. These findings demonstrate that even peripheral mechanics of auditory perception are shaped by top-down cognitive and linguistic influences.